PHYTOREMEDIATION OF CRUDE OIL CONTAMINATED SOIL USING TWO LOCAL VARIETIES OF CASTOR OIL PLANT (Ricinus communis) OF ASSAM - MINALI BAISHYA; MOHAN CHANDRA KALITA (International Journal of Pharma and Bio Sciences, 2015)
Accidental spillage of crude oil on soil makes the condition of the soil unsatisfactory for plant growth. Remediation of such soil using economic plants like castor (Ricinus communis) offers cost effective and eco-friendly method. This study aims to evaluate the growth response and remediation applicability of Castor oil plant (Ricinus communis) to crude oil contaminated soil. Here, soil contaminated with 1%, 3% and 5% (w/w) crude oil was used. The growth response of two different local varieties (green variety and red variety) of Castor was observed for a period of 180 days. Parameters taken into account for study of growth responses were plant height, stem girth, leaf area and days to flowering. Soil samples collected from the rhizosphere of the experimental plants were analyzed for total petroleum hydrocarbon (TPH) amount and an assessment of hydrocarbon utilizing bacteria (HUB) count was also done. It was observed that at 1% crude oil concentration, the plant shows more vigorous growth than that of the control (without crude oil), though at 3% and 5% plant exhibit reduction in the growth. GC-MS data analysis confirms the presence of some hydrocarbon compounds in the experimental plant roots. The amount of TPH was observed to be decreasing and the mean value of the HUB count was observed to be increasing along with time.